IMPLEMENTASI REFORMASI BIROKRASI DALAM PENGEMBANGAN PERSONEL PNS (Studi Di Akademi Militer Magelang) - Darmoko; Windy Kartika Putri; , Sambas Burhanudin; , Suhartini (PPM Sdirjianbang Akademi Militer, 2025)
Bureaucratic reform is a strategic effort in improving the effectiveness and efficiency of government administration, including in the management of human resources of the state civil apparatus (ASN). Magelang Military Academy as a military educational institution has the responsibility of managing and developing civil service personnel (PNS) to support the main tasks and functions of the Academy. This study aims to analyze the implementation of bureaucratic reform in the development of civil servant personnel at the Magelang Military Academy. The method used is a qualitative approach with data collection techniques through interviews, observations, and documentation studies. The results showed that bureaucratic reform has been implemented through the improvement of the recruitment system, increased employee competence, as well as the application of merit system in the promotion and rotation of positions. However, there are still obstacles such as resistance to change, limited resources, and administrative constraints that hinder the effectiveness of the implementation of bureaucratic reform. This study recommends strengthening regulation, increasing managerial capacity, and optimizing the use of Information Technology in Personnel Management.